ANALISIS HARGA DAN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK JAMUR TIRAM PUTIH PURWANTI (STUDI KASUS MASYARAKAT KECAMATAN KOTO SALAK) - Mega Pratiwi Mega Pratiwi; Eka Ermawati; Dini Elida Putri; Fenisi Resty (MANAJEMEN DEWANTARA, 2022)
The purpose of this study was to know price and packaged analysis of the decision to purchase the purwanti white oyster mushrooms. The method used is the quantitative method with data retrieval using a questionnaire. Data analysis techniques with validity tests, religious tests, correlation analysis, classic assumptions test, linear regression analysis, hypothetical testing. The results of the study indicate that the partial price variable affected the purchasing decision variables was shown by the processing of raw data, legible, and variable variables As much as 3,725 with the significant value of 0,000< 0.05, furthermore the packaged variables have a partial impact on the purchase decision variables indicated by data processing, quantifiable, oscillate variables At 8.496, the value of 0,000< 0.05.1Based on the results of the f that the price and packaging will have a significant impact simultaneously on the an f decision of 66.803 with a significant degree (0,000 < 0.05), which means that together the price variables and the packaging will significantly affect the decision of the purchase. Its intrinsir square value is 0.547 which means that all independent variables can explain 54.7% of the existing.